The Moroccan Poetic Journey between History and Significance - BELHADJI, Fatiha (Milev Journal of Research and Studies, 2020)
This article aims to investigate the impact of authorship on nomads that were not limited to the scattered nomads but rather exceeded them to poetic systems. The different poems have implications, and they differ in artistic value, such as the journey of Al-Abdari and the El-kafife Al-Zerhouni. The issues that the poetic trip has touched are numerous.